A HOPS Protein, MoVps41, Is Crucially Important for Vacuolar Morphogenesis, Vegetative Growth, Reproduction and Virulence in Magnaporthe oryzae - Zhang, Xiaojie; Wang, Guanghui; Yang, Chengdong; Huang, Jun; Chen, Xiaofeng; Zhou, Jie; Li, Guangpu; Norvienyeku, Justice; Wang, Zonghua (Frontiers in Plant Science, 2017)
The homotypic fusion and protein sorting protein complex (HOPS) is the first known tether complex identified in the endocytic system that plays a key role in promoting homotypic vacuolar fusion, vacuolar biogenesis and trafficking in a wide range of organisms, including plant and fungi. However, the exact influence of the HOPS complex on growth, reproduction and pathogenicity of the economically destructive rice blast fungus has not been investigated. In this study, we identified M. oryzae vacuolar protein sorting 41 (MoVps41) an accessory subunit of HOPS complex and used targeted gene deletion approach to evaluate its contribution to growth, reproduction and infectious life cycle of the rice blast fungus. Corresponding results obtained from this study showed that MoVps41 is required for optimum vegetative development of M. oryzae and observed that MoVps41 deletion mutant displayed defective vegetative growth. Our investigation further showed that MoVps41 deletion triggered vacuolar fragmentation, compromised membrane integrity and pathogenesis of the ΔMovps41 mutant. Our studies also showed for the first time that MoVps41 plays an essential role in the regulation of sexual and asexual reproduction of M. oryzae. In summary, our study provides insight into how MoVps41 mediated vacuolar fusion and biogenesis influences reproduction, pathogenesis, and vacuolar integrity in M. oryzae and also underscores the need to holistically investigate the HOPS complex in rice blast pathogen.